2023
DOI: 10.3390/molecules28041895
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Mechanism of Madecassic Acid against Staphylococcus aureus

Abstract: Antibacterial resistance has become one of the most serious problems threating global health. To overcome this urgent problem, many scientists have paid great attention to developing new antibacterial drugs from natural products. Hence, for exploring new antibacterial drugs from Chinese medicine, a series of experiments were carried out for verifying and elucidating the antibacterial activity and mechanisms of madecassic acid (MA), which is an active triterpenoid compound isolated from the traditional Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…β-Galactosidase is an enzyme that is located in the cytoplasm of bacterial cells and is involved in the metabolism of lactose. When the inner membrane of a bacterial cell is disrupted or damaged, β-galactosidase can leak out of the cell into the surrounding medium [ 35 , 36 ]. The results demonstrated that RL permeated the inner membrane in a dose-dependent manner at 0.125–1 mg/mL ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…β-Galactosidase is an enzyme that is located in the cytoplasm of bacterial cells and is involved in the metabolism of lactose. When the inner membrane of a bacterial cell is disrupted or damaged, β-galactosidase can leak out of the cell into the surrounding medium [ 35 , 36 ]. The results demonstrated that RL permeated the inner membrane in a dose-dependent manner at 0.125–1 mg/mL ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus, E. faecium, E. coli , P. aeruginosa , A. baumannii J71 and K. pneumonia J4 were routinely cultured in MH medium at 35 °C [22] . The resistant stains of candida.albicans and candida.tropical were collected from clinical department.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Strains, growth and agents S. aureus, E. faecium, E. coli, P. aeruginosa, A. baumannii J71 and K. pneumonia J4 were routinely cultured in MH medium at 35 °C. [22] The resistant stains of candida.albicans and candida.tropical were collected from clinical department. And the stander stains of candida.albicans and candida.tropical were from our lab.…”
Section: Asperbutenolide a Preparationmentioning
confidence: 99%
“…Therefore, it has become an important and urgent task to explore natural products with low toxicity and high anti-microbial activity for treating the initial stage of infection, reducing the use of antibiotics, and limiting the development of drug resistance of pathogenic microorganisms (Wei et al 2023).…”
Section: Introductionmentioning
confidence: 99%